A pinning effect for the enhanced oxidation resistance at 1600 °C of silicoboron carbonitride ceramics with the addition of MXene. (March 2022) - Bin Liang,; Liao, Xingqi; Geng, Bo; Zhu, Qishuai; Yu, Ming; Li, Jiacheng; Liu, Kangwei; Jia, Dechang; Yang, Zhihua; Zhou, Yu
Abstract: MXenes with lots of attractive mechanical and physicochemical properties have great potential in various applications. However, no mention has been made of the high-temperature properties of structural ceramics with MXenes, let alone silicoboron carbonitride (Si-B-C-N) composite ceramics over 1500 °C. The influences of MXene(Ti3 C2 Tx ) additives on the oxidation resistance of Si-B-C-N ceramics were investigated at temperatures up to 1600 °C here for the first time. Dense, adherent scales are formed on surfaces of the oxidized ceramics at 1100 °C, and the thicknesses of scales present an overall decrease with the increased addition of Ti3 C2 Tx . The addition of 3.0 wt% Ti3 C2 Tx can improve the oxidation resistance at 1600 °C due to the pinning effect of rod-like TiO2 grains mostly buried in SiO2 scales, while less addition could probably deteriorate the anti-oxidation properties. The development of Si-B-C-N composite ceramics demonstrates that MXenes are promising additives for improving high-temperature antioxidant properties of multicomponent silicon-based ceramics at least. Highlights: 2D MXene (Ti3 C2 Tx ) was incorporated into Si-B-C-N ceramics. Oxidation resistance over 1500 °C of Si-B-C-N composite ceramics was studied. A pinning effect enhanced oxidation resistance of Si-B-C-N ceramics at 1600 °C.